Color tuning of indium phosphide quantum dots for cadmium‐free quantum dot light‐emitting devices with high efficiency and color saturation. Issue 7 (July 2015) - Ippen, Christian; Greco, Tonino; Kim, Yohan; Pries, Christopher; Kim, Jiwan; Oh, Min Suk; Han, Chul Jong; Wedel, Armin
Abstract: Semiconductor quantum dots (QDs) promise facile color tuning and high color saturation in quantum‐dot light‐emitting devices (QD‐LEDs) by controlling nanoparticle size and size distribution. Here, we demonstrate how this promise can be practically realized for the cadmium‐free InP/ZnSe/ZnS multishell quantum dots. We developed a set of synthesis conditions and core/shell compositions that result in QDs with green, yellow, and red emission color. The QD‐LEDs employing these QDs show efficient electroluminescence (EL) with luminance up to 1800 cd/m 2 and efficiency up to 5.1 cd/A . The color coordinates calculated from the EL spectra clearly demonstrate the outstanding color saturation as an outcome of the narrow particle size distribution. These results prove that the performance gap between cadmium‐free and cadmium‐based QDs in QD‐LEDs is shrinking rapidly. Abstract : Semiconductor quantum dots (QDs) promise facile color tuning and high color saturation in quantum‐dot light‐emitting devices by controlling nanoparticle size and size distribution. Here, we demonstrate how this promise can be practically realized for the cadmium‐free indium phosphide/zinc selenide/zinc sulfide multishell quantum dots. We developed a set of synthesis conditions and core/shell compositions that result in QDs with green, yellow, and red emission color.